The Implications of Ontario’s Historical Oil and Gas Drilling and Abandonment Practices for Abandoning Orphan and Legacy Wells - Heagle, Dru J.; Sealey, Robert (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2023)
Oil and gas exploration in Ontario began in the mid-1800s, leading to the first oil well drilled in 1858 and the first commercial gas well drilled in 1889. These early discoveries kicked off a boom of exploration and development drilling activity, but well records were not mandatory until 1919 after the introduction of the Natural Gas Act R.S.O.1918, c. 12. The Ontario Bureau of Mines estimated 10,000 operating oil wells in the province at the turn of the 20th century, but there are only records for approximately 1,500 wells. By 1970 there were an estimated 50,000 wells drilled in the province though there are only records for 27,000 wells, indicating there may be tens of thousands of unrecorded or lost wells in southwestern Ontario. Wells that are not properly plugged are a conduit for fluid movement, including brine, natural gas, oil, and hydrogen sulphide, to move from the subsurface to the surface. Historical well abandoning regulations required wells to be plugged with inferior materials including wood, clay, and rubble. Cement was not the standard plugging material until 1964. There are orphaned and legacy wells leaking natural gas and sulphur water (groundwater containing dissolved sulphate and hydrogen sulphide) creating a risk to public safety. Orphaned and legacy wells are also a risk for subsurface energy projects including geological storage of carbon dioxide, hydrogen, and compressed air energy, because the wells may provide a pathway for injected fluids to return to the surface. This study reviews well construction, legislation, and abandonment practices in Ontario beginning in 1858 and identifies five factors impacting the plugging and abandonment of orphaned and legacy wells.Further work is required to locate unreported or lost wells and to develop new techniques to permanently plug wells to limit gas leakage, reduce greenhouse gas emissions, and improve public and environmental safety.